Religious Values in the Folklore of Cetho Temple in Jenawi District, Karanganyar Regency - Azizah, Riza Nur; Sunanda, Adyana (Universitas Muhammadiyah Surakarta, 2023)
Cetho Temple is one of Indonesia's tourist attractions that still retains Hindu religious nuances and serves as a venue for religious ceremonies. This study aims to describe and highlight the values present in Cetho Temple folklore, particularly its religious values. The approach used in this study is a qualitative descriptive method. Qualitative descriptive research employs sustainable means adapted to the realities of the field. This research was conducted based on a literature review. The data collected will be analyzed, interpreted, and synthesized to provide accurate and systematic illustrations or representations of the research findings. The data collection method employed in this study is library research. The results of this study demonstrate that the religious values embedded in the folklore of Cetho Temple are still preserved and upheld today. This tradition continues to be practiced, ensuring that those inheriting the community's or ancestors' traditions continue to maintain and care for Cetho Temple.